Skills retraining programmes for electronic laboratory technologists in universities in developing countries like Nigeria - Osaigbovo Louis Odaro; Abusonwan Sunday Bello (Technium Social Sciences Journal, 2020)
The dynamic nature of the world had resulted in state of the art electronics gadgets. This has led to calls for periodic analysis of the skills retraining programmes of electronic laboratory technologists in Universities. The study adopted the survey research design. The target population for the study was 68electronic laboratory technologists. A 60task items structured questionnaire was used for data collection. The instrument was validated by three experts and a reliability coefficient of 0.72 obtained. Data were collected and analyzed using statistical package for social sciences (SPSS, version, 24). Mean, standard deviation, Cronbach’s Alpha, and principal component analysis were the statistical tools used for data analysis. Findings in the study revealed that 5 major skills retraining programmes are often deployed by electronic laboratory technologists and therefore requires module development. The study therefore recommend that a committee of experts should be inaugurated urgently to design a comprehensive module for electronic laboratory technologists that will include these five major skills retraining programmes and should be reviewed periodically.